46th AIAA Thermophysics Conference 2016
DOI: 10.2514/6.2016-4432
|View full text |Cite
|
Sign up to set email alerts
|

Application of A New Thermal-Mechanical Coupling Solver for Ablation

Abstract: Thermo-mechanical analysis of ablative materials is of great importance to Thermal Protection System design. A coupling method for thermo-mechanical and ablation response model is proposed using a Finite Volume approach. This method is capable of simulating both transient and static structural response. The solver is verified using a series of test cases and then fully coupled to a material response code. Coupled results show that the temperature field has a significant effect on mechanical performance and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…3,4 The data gained in such experiments will be provided as validation data for high fidelity material response codes, 6,5 and spallation modeling efforts. 7,8 For the investigation of gas-surface interactions as conducted in the HYMETS facility earlier but without spatial resolution, 9 a setup was developed which images the stagnation line in front of a sample onto the entrance slit of a spectrometer. This arrangement provided an effective spatial resolution of 0.3 mm over a length of 22 mm covering the entire distance from the sample surface to a position upstream of the bow shock.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The data gained in such experiments will be provided as validation data for high fidelity material response codes, 6,5 and spallation modeling efforts. 7,8 For the investigation of gas-surface interactions as conducted in the HYMETS facility earlier but without spatial resolution, 9 a setup was developed which images the stagnation line in front of a sample onto the entrance slit of a spectrometer. This arrangement provided an effective spatial resolution of 0.3 mm over a length of 22 mm covering the entire distance from the sample surface to a position upstream of the bow shock.…”
Section: Introductionmentioning
confidence: 99%
“…Engineering practice has shown that rock bolting is more effective in enhancing roadways than metal support, wood support and joint support [3][4]. Being the most widely used mode of rock anchoring, resin anchoring embeds the anchor into the surrounding rock of the roadway, and bonds it with the rock by unsaturated polyester [4][5][6][7][8][9]. Compared with cement mortar and other rock anchoring materials, the resin material solidifies fast, realizes efficient support, and facilitates construction [10][11][12].…”
Section: Introductionmentioning
confidence: 99%